Analysis of retinal nerve fibre layer, visual evoked potentials and relative afferent pupillary defect in multiple sclerosis patients. Issue 1 (January 2016) - Chilińska, Adriana; Ejma, Maria; Turno-Kręcicka, Anna; Guranski, Konstanty; Misiuk-Hojlo, Marta
Highlights: We evaluated RNFL, pVEPs studies and RAPD changes in multiple sclerosis patients. pVEPs were more frequently abnormal than RNFL in eyes with and without optic neuritis (ON). RNFL damage in eyes without ON may indicate neurodegenerations in CNS of MS patients. Abstract: Objective: The aim of this study was to analyse retinal nerve fibre layer (RNFL), pattern-reversal visual evoked potentials (pVEPs) and relative afferent pupillary defect (RAPD) changes in multiple sclerosis (MS) patients with the consideration of past optic neuritis (ON). Methods: Ophthalmological, neurological, OCT, RNFL and pVEP studies were conducted in 59 MS patients. RAPD tests were performed in 47 of them. Control group consisted of 28 healthy volunteers. Results: Abnormal RNFL was found in 59% of cases of eyes with ON and 28% of eyes without ON. In eyes with ON, significantly lower RNFL values were indicated in the temporal and lower quadrants. Elongation of pVEP latency was found in 83% of eyes with ON and 60% of eyes without ON. The average value of pVEP latency was larger and the amplitude was lower in the subgroup of eyes with RNFL at the borderline or below the norm. RAPD was observed only in eyes with ON and with RNFL thinning. No association was found between the RAPD and pVEP parameters. Conclusions: VEPs were more frequently abnormal than RNFL in MS patients. RNFL damage in eyes without ON may indicate neurodegenerations in CNS of MS patients; it can also be the consequence of subclinical ON. Significance: An analysis of RNFL and VEP can be useful for evaluating the optic nerve in MS patients.